False-positive Serum IgM/IgG to SARS-CoV-2 in a Rare Pulmonary Neuroendocrine Carcinoma with Ocular Metastasis: A Case Report - Pratomo, Irandi P; Priyonugroho, Gatut; Ramdhani, Aris; Zamroni, Dian; Salamah, Thariqah; Susanto, Yayi D.B; Zairinal, Ramdinal A; Witjaksono, Annisa N; Aditianingsih, Dita; Zaini, Jamal (UI Scholars Hub, 2022)
The Coronavirus disease 2019 (COVID-19) pandemic impacts pulmonary cancer management since it shares similar clinical features and creates fear among patients to visit hospitals due to possible in-hospital disease transmission. We report a patient who presented with a rare case of a pulmonary neuroendocrine tumor with an ocular involvement, which, unfortunately, experienced a delay in diagnostics. The first hospitalization was due to superior vena cava syndrome, pleural and pericardial effusions, and swollen left eye. The patient was diagnosed with pulmonary cancer, released after the symptoms were relieved, and expected to visit a referral hospital for further diagnostics and treatments. The patient returned two weeks later with progressing disease, an ocular metastasis, and a reactive serum IgM/IgG to SARS-CoV-2; serial qPCR tests consistently returned negative. The patient was treated with the best supportive care before succumbing to death. Biopsy showed pulmonary tumor cells consistent with a neuroendocrine tumor. Fear of the pandemic makes patients reluctant to seek help from medical facilities. Pulmonary TBC has similar symptoms to pulmonary cancer, which can pose another challenge in diagnosing pulmonary cancer in TB-endemic countries. Thus, patients often present with advanced-stage pulmonary cancer with rare ocular metastasis, as in this report.